SYMBOLISM IN SOUNDTRACKS OF THE LION KING MOVIE - Sri Susilawatin; Baharuddin; Eka Fitriana (Program Studi Pendidikan Bahasa Inggris, 2021)
The research was aimed to find out the kind of symbol in soundtracks of The Lion King Movie. This research follows a descriptive qualitative approach to identify, describe and analyze the phenomenon of symbolism. The data were about symbolism taken from seven songs of soundtracks in The Lion King Movie. The data were analyzed based on Jung’s (1964) theory of symbolism, and semiotics theory to interpret the data. The findings showed that there are found 24 symbols in seven soundtracks of The Lion King Movie, which are divided into two kinds: conventional symbol and contextual symbol. There are 18 conventional symbols found in seven soundtracks and there are only 6 contextual symbols found in five soundtracks of The Lion King Movie.